Teaching English to Teenagers and How to Gain Their Interest - Mulyadi Mulyadi (Universitas PGRI Palembang, 2015)
AbstrakTeaching English to teenagers and how gain their interest is still consider to be hot issue. Teenagers are the most difficult age group to teach. However, if the teachers are able to manage them well, teen classes can also be fun and very rewarding for both the teacher and students. It is believed that the materials that the teacher uses in the classroom are a crucial factor in deciding if a teens class is successful or not. Therefore, it is important to provide lessons which keep them interested. If the students are not interested in the material we are using, it is probable that both students and teacher will end up bored and frustrated. While many of us may be obliged to use certain course books and other material that may not always stimulate our students, it is important to adapt this material or supplement it with activities that bring the students to life and encourage them to express themselves. If the teacher shows that she is interested in her students' opinions and is prepared to adapt her lessons after listening to these opinions, this can have a very positive effect on the atmosphere in the classroom.Keywords: Teaching, teenager, interestAbstractTeaching English to teenagers and how gain their interest is still consider to be hot issue. Teenagers are the most difficult age group to teach. However, if the teachers are able to manage them well, teen classes can also be fun and very rewarding for both the teacher and students. It is believed that the materials that the teacher uses in the classroom are a crucial factor in deciding if a teens class is successful or not. Therefore, it is important to provide lessons which keep them interested. If the students are not interested in the material we are using, it is probable that both students and teacher will end up bored and frustrated. While many of us may be obliged to use certain course books and other material that may not always stimulate our students, it is important to adapt this material or supplement it with activities that bring the students to life and encourage them to express themselves. If the teacher shows that she is interested in her students' opinions and is prepared to adapt her lessons after listening to these opinions, this can have a very positive effect on the atmosphere in the classroom. Keywords: Teaching, teenager, interest